2020
DOI: 10.1016/j.ijengsci.2019.103208
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic phenomena and crack propagation in dissimilar elastic lattices

Abstract: Dynamic Mode III interfacial fracture in a dissimilar square-cell lattice, composed of two contrasting mass-spring lattice half-planes joined at an interface, is considered. The fracture, driven by a remotely applied load, is assumed to propagate at a constant speed along the interface. The choice of the load allows the solution of the problem to be matched with the crack tip field for a Mode III interfacial crack propagating between two dissimilar continuous elastic materials. The lattice problem is reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 74 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…They are of great importance in problems concerning the dynamic propagation of cracks in discrete systems, as discussed by Marder and Gross (1995) and Slepyan (2002) for uniform media and in successive works (Nieves et al, 2013) for non-uniform lattices. Similar localized phenomena may play a substantial role in non-uniform crack propagation as evidenced in (Piccolroaz et al, 2020), where lattice dissimilarity has been shown to promote or diminish localized deformations around the faces of the crack. Trapped modes associated with Rayleigh-Bloch waves in systems incorporating periodic gratings or periodic arrays of resonators were analyzed by Porter and Evans (1999), Porter and Evans (2005), Linton and McIver (2002) and Antonakakis et al (2014) for scalar problems, by Colquitt et al (2015) for vector systems and by Haslinger et al (2017) and Morvaridi et al (2018) for plates.…”
Section: Introductionmentioning
confidence: 80%
“…They are of great importance in problems concerning the dynamic propagation of cracks in discrete systems, as discussed by Marder and Gross (1995) and Slepyan (2002) for uniform media and in successive works (Nieves et al, 2013) for non-uniform lattices. Similar localized phenomena may play a substantial role in non-uniform crack propagation as evidenced in (Piccolroaz et al, 2020), where lattice dissimilarity has been shown to promote or diminish localized deformations around the faces of the crack. Trapped modes associated with Rayleigh-Bloch waves in systems incorporating periodic gratings or periodic arrays of resonators were analyzed by Porter and Evans (1999), Porter and Evans (2005), Linton and McIver (2002) and Antonakakis et al (2014) for scalar problems, by Colquitt et al (2015) for vector systems and by Haslinger et al (2017) and Morvaridi et al (2018) for plates.…”
Section: Introductionmentioning
confidence: 80%
“…In fact, many studies have shown that standard microstructures can achieve a reduction in the energy release ratio and even failure [29,37,45,60]. In recent years, elastic wave metamaterials have been extensively studied because of their superior abilities, so it is natural to apply them in practical engineering in which the dynamic fracture should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…is the composition of elastic structures via periodic lattices [1][2][3][4][5][6][7][8][9]. In these structures, different effects related to out-of-plane or in-plane deformations, the presence of bending moment or prestress have been explored [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%